1995
DOI: 10.1016/0028-3932(95)00045-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased corpus callosum size in musicians

Abstract: Al~tract--Using in-vivo magnetic resonance morphometry it was investigated wbetheT the midsagittal area of the corpus callosum (CC) would differ between 30 professional musicians and 30 age-, sex-and handedness-matched controls. Our analyses revealed that the anterior half of the CC was significantly larger in musicians. This difference was due to the larger anterior CC in the subgroup of musicians who had begun musical training before the age of 7. Since anatomic studies have provided evidence for a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
442
2
20

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 645 publications
(486 citation statements)
references
References 39 publications
22
442
2
20
Order By: Relevance
“…All correlations were negative, indicating higher diffusivity for earlier onset (table 1). Schlaug et al (1995a) found enlarged anterior callosa only in a subgroup of musicians who had started musical training before the age of 7. Therefore, we regrouped the musicians by a median split (median of onset = 6.25 years) and assigned them to an early onset group (n = 13, mean age = 23.8 ± 3.0, mean onset = 5.0 ± 0.7) and a late onset group (n = 13, mean age = 25.38 ± 2.6, mean onset = 8.6 ± 1.1).…”
Section: Onset Of Musical Trainingmentioning
confidence: 93%
See 4 more Smart Citations
“…All correlations were negative, indicating higher diffusivity for earlier onset (table 1). Schlaug et al (1995a) found enlarged anterior callosa only in a subgroup of musicians who had started musical training before the age of 7. Therefore, we regrouped the musicians by a median split (median of onset = 6.25 years) and assigned them to an early onset group (n = 13, mean age = 23.8 ± 3.0, mean onset = 5.0 ± 0.7) and a late onset group (n = 13, mean age = 25.38 ± 2.6, mean onset = 8.6 ± 1.1).…”
Section: Onset Of Musical Trainingmentioning
confidence: 93%
“…The hypothesis that an early onset of musical training may be crucial for white matter plasticity in the brain was derived from Schlaug et al (1995a). They reported enlarged anterior callosa only in the subgroup of musicians which had started musical training before the age of 7, but not in the subgroup with later onset.…”
Section: Onset Of Musical Trainingmentioning
confidence: 99%
See 3 more Smart Citations